9th May 2018 the day Malaysians finally opened their [eyes] and saved the nation! - Angus, Harold J. (2018)
The ruling coalition that had governed Malaya since Merdeka of 1957 was vanquished in the Perfect Storm to overthrow the powerful elites without violence or even a single drop of bloodshed.